Maternal perception of fetal motor activity. Issue 6199 (10th November 1979) - Hertogs, K; Roberts, A B; Cooper, D; Griffin, D R; Campbell, S
Abstract : A technique using real-time ultrasound for comprehensive recording of fetal motor activity was used in 20 subjects in the third trimester of pregnancy. Maternal awareness of fetal movement correlated with the number of fetal parts contributing to the movement but not with maternal parity or obesity, gestational age, placental site, or duration of the fetal movement. Some subjects recorded fetal breathing, passive fetal displacement, and Braxton Hicks's contractions as fetal movement. Most of our subjects were consistent and accurate in their perception of major fetal movements, but a few were inconsistent and one was completely unaware of major fetal movements. These results suggest that kick counts kept by most mothers will be accurate. Low counts of fetal movement should be an indication for fetal monitoring by other means and not, unconfirmed, for intervention.